Design And Simulation Of Static Var Compensator For Voltage Sags Mitigation - Md yusof, Arshad (2002)
Modem power networks are loaded more heavily than ever before to fully utilize the existing transmission facilities while power quality has become an important issue in power system, this is due to the fact that the usage of power electronic equipment and electronic-based loads, which are sensitive to power quality has increased, and thus normal operations in industrial and commercial environments are becoming more vulnerable to power quality problems. One of the problems associated with power quality is voltage sag. Voltage sag is a major power quality problem. It occurs because most voltage sags are due to short circuit on transmission and distribution lines. High technology industries are highly sensitive to voltage sags. A small voltage sag for several cycle, (short duration) is sufficient to interrupt the operation of the facility resulting in costly downtime.Traditional voltage regulating devices such as electromechanical transformer taps and shunt capacitor have been used extensively at the transmission and distribution. However, they are too slow to response to correct voltage sags. This problem can be overcome by replacing them with power-electronics based devices known as Flexible Alternating Currents Transmission System (FACTS). FACTS devices can provide a real-time control of transmission line impedance, voltage magnitude and phase angle. With advancement of high power electronics, fast response of FACTS device is now available. Through proper coordination, they can be utilized to control system power flow, increase power transfer capabilities, improve system transient stability, and damp power system oscillations. Static Var Compensator, SVC is a shunt connected FACTS device having capability of supplying reactive power and thus could protect the system from the potential threats of voltage sags. The objective of this research is to investigate and design SVC for voltage sags mitigation on a small test power system. This work has indicated SVC has the potential to mitigate voltage sag if properly designed and located.